Epiphytic macrolichen indication of air quality and climate in interior forested mountains of the Pacific Northwest, USA. (June 2015) - Root, Heather T.; Geiser, Linda H.; Jovan, Sarah; Neitlich, Peter
Highlights: We develop lichen bioindicators of N pollution in dry forests of the Pacific Northwest. Lichen communities are positively related to monitored ambient N concentrations. Lichen N concentrations are positively related to monitored ambient N concentrations. Lichen communities are naturally more eutrophic in climates with more moisture stress. Lichen communities indicate climate regimes independently of air quality. Abstract: Biomonitoring can provide cost-effective and practical information about the distribution of nitrogen (N) deposition, particularly in regions with complex topography and sparse instrumented monitoring sites. Because of their unique biology, lichens are very sensitive bioindicators of air quality. Lichens lack a cuticle to control absorption or leaching of nutrients and they dynamically concentrate nutrients roughly in proportion to the abundance in the atmosphere. As N deposition increases, nitrogen-loving eutrophic lichens become dominant over oligotrophic lichens that thrive in nutrient-poor habitats. We capitalize on these characteristics to develop two lichen-based indicators of air-borne and depositional N for interior forested mountain ecosystems of the Pacific Northwest and calibrate them with N concentration measured in PM2.5 at 12 IMPROVE air quality monitoring sites in the study area. The two lichen indices and peak frequencies of individual species exhibited continuous relationships with inorganic N pollution throughout the range of N in ambient PM2.5, suggesting that the designation of a critical level or critical load is somewhat arbitrary because at any level above background, some species are likely to experience adverse impacts. The concentration of N in PM2.5 near the city of Spokane, Washington was the lowest measured at an instrumented monitoring site near known N pollution sources. This level, 0.37 μg/m 3 /year, served as a critical level, corresponding to a concentration of 1.02% N in the lichen Letharia vulpina, which is similar to the upper end of background lichen N concentrations measured elsewhere in the western United States. Based on this level, we estimate critical loads to be 1.54 and 2.51 kg/ha/year of through-fall dissolved inorganic N deposition for lichen communities and lichen N concentration, respectively. We map estimated fine-particulate (PM2.5 ) N in ambient air based on lichen community and lichen N concentration indices to identify hotspots in the region. We also develop and map an independent lichen community-based bioclimatic index, which is strongly related to gradients in moisture availability and temperature variability. Lichen communities in the driest climates were more eutrophic than those in wetter climates at the same levels of N air pollution.